CONGENITAL HYPOTHYROIDISM BY ATHYREOSIS: About a new case from the Dysmorphology, Congenital and Developmental Anomalies Unit - AKHRIF, MARIAM (European Journal of Applied Sciences, 2021)
The objective of this work is to contribute to the promotion of neonatal screening for congenital hypothyroidism in our daily practice. In the Kingdom of Morocco, neonatal screening is in the process of generalization, but some newborns escape this screening activity. The authors report the case of a female infant aged 14 months, resulting from a pregnancy followed and carried to term in a maternity hospital. She presented with a delay of psychomotor acquisitions with chronic constipation, macroglossia and respiratory difficulties. The clinical examination found a staturoponderal delay, facial puffiness, a hoarseness of the voice, an umbilical hernia and a psychomotor delay concerning the holding of the head and the sitting position. The biological assessment showed a deep peripheral hypothyroidism. The cervical ultrasound showed the absence of thyroid gland visualization. Thyroid scintigraphy with Tc99m showed the total absence of fixation of the tracer at the level of the thyroid lodge, absence of ectopic focus at the level of the axis of the thyroglossal tract. The bone age was in favor of the bone age of a newborn. Through this case, the authors underline the importance of carrying out neonatal screening for congenital hypothyroidism by all physician taking care all newborns while awaiting the generalization throughout the Morocco. All this, to avoid the serious and avoidable complications of this disease.